The Effect of Curcuma (Curcuma xanthorrhiza Roxb.) Extract Capsule Treatment on Mice Blood Glucose Level: Pengaruh Pemberian Kapsul Ekstrak Temulawak (Curcuma xanthorrhiza Roxb.) terhadap Kadar Glukosa Darah pada Mencit - Diah Nurcahyani (Akademi Farmasi Surabaya, 2022)
Diabetes melitus is a metabolic disorder with escalating blood glucose level (hyperglycemic) symptom. One of endemic plant in Indonesia which have antidiabetic properties potency is curcuma. This background leads to this research that was conducted to determines the effect of various curcuma extract capsule dose treatment to lowering mice blood glucose. This research was used glucose induced mice that were grouped into three groups: Group I (Negative control) aqua destilata treated group, Group II (Dose 1) curcuma extract capsule dose 18 mg/kgBW treated group, and Group III (Dose 2) curcuma extract capsule dose 20 mg/kgBW treated group. After 7 days of treatment, blood glucose level negative control group is 185 mg/dl, curcuma extract capsule dose 1 is 123 mg/dl, and dose 2 is 101 mg/dl. Curcuma extract capsule treated groups showed significant different blood glucose level with negative control treated group. This could be concluded that curcuma extract capsule has effect as antihyperglycemic on glucose 5% induced mice.